Electrophoretic karyotyping of Hypsizygus marmoreus and evaluation of variation among its basidiospores. Issue 2 (30th September 2014) - Lee, Song Hee; Kim, Min Keun; Lee, Mi Kyoung; Kim, Na Ri; Lee, Chang‐Yun; Lee, Hyun‐Sook
Abstract The molecular karyotype of Hypsizygus marmoreus was explored by contour‐clamped homogeneous electric field gel electrophoresis. Eleven chromosomal bands were separated from the dikaryotic mycelia of H. marmoreus (strain Hm 3‐10), and the chromosomes ranged in size from 1.9 to 5.8 Mb. The total genome size of the strain was estimated to be 36.3 Mb. The chromosome numbers were also confirmed by telomere fingerprinting, and 22 telomeric bands were identified. This result suggests that 11 chromosomes exist in Hm 3‐10. The marker sequences for each chromosome were determined and were applied to identify each chromosome. Karyotyping and Southern blot analysis revealed that the size of chromosomes in the basidiospores were greatly different from those of parental dikaryon Hm 3‐10 cells.